Citrus fruit : biology, technology and evaluation - Ladaniya, Milind (Academic, 2008)
Citrus rank among top three fruits of the world with respect to area and production. Grown commercially in more than 140 countries around the world, world production of citrus fruit has experienced continuous growth in the last decades of the twentieth century with total annual citrus production over 105 million tons between 2000 and 2004. These fruits are commercially important contributing $6-8 billion (US) annually to the world economy and providing jobs to millions of people around the world in harvesting, handling, transportation, storage and marketing. Post harvest biology and technology of citrus fruits is gaining importance as the therapeutic value of citrus fruits is realized and supported by the increase in health awareness among the general public. The purpose of this book is to provide the most comprehensive reference on citrus fruit biology, biotechnology and quality. Basic and applied scientific information is interwoven to serve the researcher, marketer, scientist, nutritionist, or dietician. With discussions of fruit morphology, anatomy, physiology and biochemistry and chapters on growth phases, maturity standards, grades and physical and mechanical characteristics of citrus trees, this book provides the foundation for understanding growth, harvest and post harvest aspects of these important plants. Insect-pests and diseases, irrigation, nutrition and rootstocks are also explored. * Provides practical tips for post harvest management. * Includes all aspects of citrus fruit biology, technology and quality evaluation. * Discusses biotechnological applications and potential fresh citrus fruit quality improvement * Evaluates medicinal and therapeutic applications and recent clinical findings * Exhaustive glossary included.